Coating method of ZnS optical thin film and application of ZnS optical thin film in preparation of infrared detector chip
Through the method of ion source cleaning and vapor resistance coating, a high-temperature-resistant ZnS optical film is formed, which solves the problem of defiling of the ZnS optical film under high temperature conditions and is suitable for the preparation of infrared detector chips.
Patent Information
- Application Number
- CN202411925323.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-21
AI Technical Summary
ZnS optical films are prone to defiling under high temperature conditions, especially after experiencing high temperature conditions of 300°C.
The substrate is cleaned by an ion source, and then the vapor-resistant coating is carried out at a temperature of 100°C to 110°C and a screen voltage of 700 V to 900 V to form a ZnS film and heat treatment is performed to improve its high temperature resistance.
It achieves no defiling under high temperature and shredding conditions, improves the high temperature resistance of ZnS optical film, and is suitable for the preparation of infrared detector chips.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of instrumentation engineering, and in particular to a ZnS optical film coating method and an application thereof in preparing an infrared detector chip. Background Art
[0002] ZnS optical thin film coating is an important step in the preparation of infrared detector chips in this industry. ZnS can be deposited on the wafer surface at a relatively low temperature, but it is prone to film stripping, especially after being exposed to high temperatures of 300°C. Therefore, in order to solve this serious film stripping phenomenon, it is urgent to conduct in-depth research on the structure and preparation method of ZnS optical thin films. Summary of the invention
[0003] In view of this, the technical problem to be solved by the present invention is to provide a ZnS optical film coating method and its application in the preparation of infrared detector chips. The coating method provided by the present invention can prepare a high-temperature resistant ZnS optical film, which will not peel off after being subjected to high temperature and scratching.
[0004] The present invention provides a ZnS optical thin film coating method, comprising the following steps: S1) Clean the substrate with an ion source for 10 min to 15 min at a screen voltage of 650 V to 700 V; S2) performing evaporation coating on the substrate cleaned in step S1) at a temperature of 100° C. to 110° C. and a screen voltage of 700 V to 900 V using an ion source to sequentially form ZnS films on both sides of the substrate; S3) heat-treating the substrate after the coating in step S2).
[0005] The inventors of the present application creatively discovered that cleaning the substrate with a high-energy ion source and then performing resist evaporation coating with the assistance of high-ion source energy can improve the high-temperature resistance of the formed ZnS optical film, and the film will not peel off at high temperatures or be subsequently scratched.
[0006] The present invention first uses an ion source to clean the substrate for 10 min to 15 min at a plate voltage of 650 V to 700 V. The present invention controls the plate voltage to be 650 V to 700 V, so that the substrate can be cleaned by a high-energy ion source. The ion source of the present invention is a Kaufman source. The substrate of the present invention is a double-throw wafer.
[0007] After the substrate is cleaned, the present invention uses an ion source to assist in performing evaporation-resistant coating on the cleaned substrate at a temperature of 100°C to 110°C and a screen voltage of 700 V to 900 V, and sequentially forms ZnS films on both sides of the substrate. Specifically, the present invention places the cleaned substrate in a coating vessel, and uses a vacuum coating machine to perform evaporation-resistant coating on the cleaned substrate at a temperature of 100°C to 110°C. When performing evaporation-resistant coating, the screen voltage is controlled to be 700 V to 900 V, and the current of the ion source is controlled to be 10A to 20A, the anode voltage of the ion source is 60V to 80V, and the beam current of the ion source is 45 mA to 60 mA, so that the substrate can be film-formed with the assistance of a high-energy ion source.
[0008] The evaporation barrier coating of the present invention is carried out at a current of 400A-500A. Specifically, the evaporation barrier coating is controlled to be carried out at a current of 400A-500A by controlling the current flowing through the coating vessel.
[0009] The present invention performs evaporation barrier coating to sequentially form ZnS films on both side surfaces of the substrate, the coating rate of the evaporation barrier coating is below 10 Å / s, and the thickness of the formed ZnS film is 1 KA-15 KA.
[0010] After the ZnS film is formed on both sides of the substrate in sequence, the substrate after coating is subjected to heat treatment to complete the coating. The heat treatment temperature of the present invention is 300°C to 400°C, preferably 350°C; the heat treatment time is 3 h to 6 h.
[0011] The present invention also provides an application of the coating method described in any of the above technical solutions in the preparation of infrared detector chips. The coating method provided by the present invention can achieve the deposition of ZnS optical thin films on wafers at a temperature of 110°C, and has strong high temperature resistance and scratch resistance, and is very suitable for the preparation of infrared detector chips.
[0012] The present invention provides a coating method of a ZnS optical film and its application in the preparation of an infrared detector chip. The present invention provides a coating method of a ZnS optical film, comprising the following steps: S1) at a screen voltage of 650 V to 700 V, a substrate is cleaned for 10 min to 15 min using an ion source; S2) at a temperature of 100°C to 110°C and a screen voltage of 700 V to 900 V, the substrate cleaned in step S1) is subjected to evaporation assisted by an ion source, and a ZnS film is sequentially formed on both sides of the substrate; S3) the substrate after coating in step S2) is subjected to heat treatment. The coating method of a ZnS optical film provided by the present invention can realize the deposition of a ZnS optical film on a wafer under a temperature of 110°C, and has strong high temperature resistance and anti-scratch properties, simplifies the film structure, reduces the cost of optical film investment, and is suitable for coating a ZnS optical film on a wafer at around 110°C, and the subsequent ZnS optical film needs to undergo a high temperature environment process. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a schematic diagram of the structure of a double-polished wafer with ZnS film layers evaporated on both sides of the present invention; Figure 2 This is a micrograph of a 1KA thick ZnS optical film just taken out of a degassing furnace after being treated at 350°C. Figure 3 This is a micrograph of a 1KA thick ZnS optical film after film drawing experiment; Figure 4 This is a micrograph of a 1KA thick ZnS optical film after slicing; Figure 5 This is a micrograph of a 2KA thick ZnS optical film just taken out of a degassing furnace after being treated at 350°C. Figure 6 This is a micrograph of a 2KA thick ZnS optical film after film drawing experiment; Figure 7 This is a micrograph of a 2KA thick ZnS optical film after slicing; Figure 8 This is a micrograph of a 7.7KA thick ZnS optical film just taken out of a degassing furnace after being treated at 350°C. Fig. 9 This is a micrograph of a 7.7KA thick ZnS optical film after film drawing experiment; Fig.10 This is a micrograph of a 7.7KA thick ZnS optical film after slicing; Fig.11This is a micrograph of a 13KA thick ZnS optical film just taken out of a degassing furnace after being treated at 350°C. Fig.12 This is a micrograph of a 13KA thick ZnS optical film after film drawing experiment; Fig.13 This is a micrograph of a 13KA thick ZnS optical film after slicing. DETAILED DESCRIPTION
[0014] The present invention discloses a coating method of a ZnS optical thin film and its application in the preparation of an infrared detector chip. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0015] The present invention deposits ZnS film layers on both sides of a double-polished wafer. Figure 1 As shown, Figure 1 This is a schematic diagram of the structure of a double-polished wafer with ZnS film layers evaporated on both sides of the present invention.
[0016] The present invention will be further described below in conjunction with embodiments: Example 1 First, the double-polished wafer was cleaned using an ion source, where the cleaning time was 10 minutes and the screen voltage was 650V. Then, a vacuum coating machine capable of resisting evaporation coating was used to coat ZnS on the surface of the double-polished wafer by resisting evaporation at a coating rate of less than 10 Å / s at a temperature of 110°C. Finally, ZnS was coated on the other side of the double-polished wafer in the same way, and a ZnS optical film with a thickness of 1KA was prepared on both sides of the double-polished wafer. The power of the machine increased reasonably. During coating, the molybdenum boat current was 500A, the ion source current was 13A, the beam current was 50mA, and the ion source anode voltage was maintained at 70V. During ion source-assisted coating, the screen voltage was 800V, and it was ensured that no arc extinguishing would occur during the coating process.
[0017] After that, a degassing furnace was used to keep the temperature at 350℃ for 5 hours. Then, a film pulling experiment was carried out using tape, and the results showed that no film peeling phenomenon occurred. Finally, a dicing machine was used for dicing and high-speed rotation cleaning and drying.
[0018] Example 2 First, the double-polished wafer was cleaned using an ion source, where the cleaning time was 10 minutes and the screen voltage was 700V. Then, a vacuum coating machine capable of resisting evaporation coating was used to coat ZnS on the surface of the double-polished wafer at a coating rate of less than 10 Å / s at a temperature of 110°C. Finally, ZnS was coated on the other side of the double-polished wafer in the same way, and a ZnS optical film with a thickness of 1KA was prepared on both sides of the double-polished wafer. The power of the machine increased reasonably. During coating, the molybdenum boat current was 500A, the ion source current was 13A, the beam current was 50mA, and the ion source anode voltage was maintained at 80V. Among them; the screen voltage was 850V during ion source assisted coating, and it was ensured that arc extinguishing would not occur during the coating process.
[0019] After that, the degassing furnace was used to keep the temperature at 350°C for 6 hours. Then, the film pulling test was carried out using tape, and the results showed that no film peeling phenomenon occurred.
[0020] Comparative Example 1 First, the double-polished wafer was cleaned using an ion source, where the cleaning time was 10 minutes and the screen voltage was 300V. Then, a vacuum coating machine capable of resist evaporation coating was used to coat ZnS on the surface of the double-polished wafer at a coating rate of less than 10 Å / s at a temperature of 110°C. Finally, ZnS was coated on the other side of the double-polished wafer in the same way, and a ZnS optical film with a thickness of 1KA was prepared on both sides of the double-polished wafer. The power of the machine increased reasonably. During coating, the molybdenum boat current was 500A, the ion source current was 13A, the beam current was 50mA, and the ion source anode voltage was maintained at 70V. During ion source-assisted coating, the screen voltage was 300V, and it was ensured that arc extinguishing would not occur during the coating process.
[0021] After that, the degassing furnace was used to keep the temperature at 350°C for 2 hours. Then, a film pulling experiment was carried out using an adhesive tape, and the results showed that the film peeling phenomenon occurred.
[0022] Comparative Example 2 First, the double-polished wafer was cleaned using an ion source, where the cleaning time was 10 minutes and the screen voltage was 300V. Then, a vacuum coating machine capable of resisting evaporation coating was used to coat ZnS on the surface of the double-polished wafer at a coating rate of less than 10 Å / s at a temperature of 80°C. Finally, ZnS was coated on the other side of the double-polished wafer in the same way, and a ZnS optical film with a thickness of 1KA was prepared on both sides of the double-polished wafer. The power of the machine increased reasonably. During coating, the molybdenum boat current was 500A, the ion source current was 13A, the beam current was 50mA, and the ion source anode voltage was maintained at 70V. During ion source-assisted coating, the screen voltage was 300V, and it was ensured that no arc extinguishing would occur during the coating process.
[0023] After that, the degassing furnace was used to keep the temperature at 350°C for 2 hours. Then, a film pulling experiment was carried out using an adhesive tape, and the results showed that the film peeling phenomenon occurred.
[0024] Comparative Example 3 First, the double-polished wafer was cleaned using an ion source, where the cleaning time was 10 minutes and the screen voltage was 350V. Then, a vacuum coating machine capable of resisting evaporation coating was used to coat ZnS on the surface of the double-polished wafer at a coating rate of less than 10 Å / s at a temperature of 70°C. Finally, ZnS was coated on the other side of the double-polished wafer in the same way, and a ZnS optical film with a thickness of 1KA was prepared on both sides of the double-polished wafer. The power of the machine increased reasonably. During coating, the molybdenum boat current was 500A, the ion source current was 13A, the beam current was 50mA, and the ion source anode voltage was maintained at 80V. During ion source-assisted coating, the screen voltage was 400V, and it was ensured that arc extinguishing would not occur during the coating process.
[0025] After that, the degassing furnace was used to keep the temperature at 350°C for 2 hours. Then, a film pulling experiment was carried out using an adhesive tape, and the results showed that the film peeling phenomenon occurred.
[0026] The experimental conditions and film drawing test results of the above Examples 1-2 and Comparative Examples 1-3 are summarized in Table 1: Table 1
[0027] Example 3 Compared with Example 1, the difference is that the high temperature holding time at 350° C. is 8 h.
[0028] Microscopic observation of a 1KA thick ZnS optical film just taken out of a degassing furnace after high temperature treatment at 350°C. Figure 2 As shown, Figure 2This is a micrograph of a 1KA thick ZnS optical film just taken out of a degassing furnace after being treated at 350°C.
[0029] The ZnS optical film with a thickness of 1KA after high temperature insulation treatment at 350℃ was subjected to a film pulling experiment using adhesive tape. Figure 3 As shown, Figure 3 This is a micrograph of a 1KA thick ZnS optical film after film pulling experiment.
[0030] After the film drawing experiment, the ZnS optical film with a thickness of 1KA was diced and cleaned and dried with a dicing machine at high speed, and the film effect was observed under a microscope. Figure 4 As shown, Figure 4 This is a micrograph of a 1KA thick ZnS optical film after slicing.
[0031] In summary, when the ZnS film thickness is 1KA, Figure 2 It can be found that the optical film is in good condition after being kept at 350℃ for 8 hours. Figure 3 It was found that after the film pulling experiment, the quality of the film layer was still good. Figure 4 It was found that there was no film peeling at the cutting edge and the film was in good condition.
[0032] Example 4 Compared with Example 3, the difference is that a ZnS optical film with a thickness of 2KA is prepared on both sides of the double-polished wafer.
[0033] Microscopic observation of a 2KA thick ZnS optical film just taken out of a degassing furnace after high temperature treatment at 350°C. Figure 5 As shown, Figure 5 This is a micrograph of a 2KA thick ZnS optical film just taken out of a degassing furnace after being treated at 350°C.
[0034] The ZnS optical film with a thickness of 2KA after high temperature insulation treatment at 350℃ was subjected to film pulling experiment using adhesive tape. Figure 6 As shown, Figure 6 This is a micrograph of a 2KA thick ZnS optical film after film pulling experiment.
[0035] The ZnS optical film with a thickness of 2KA after the film drawing experiment was diced and cleaned and dried with a dicing machine at high speed, and the film effect was observed under a microscope. Figure 7 As shown, Figure 7 This is a micrograph of a 2KA thick ZnS optical film after slicing.
[0036] In summary, when the ZnS film thickness is 2KA, Figure 5It can be found that the optical film is in good condition after being kept at 350℃ for 8 hours. Figure 6 It was found that after the film pulling experiment, the quality of the film layer was still good. Figure 7 It was found that there was no film peeling at the cutting edge and the film was in good condition.
[0037] Example 5 Compared with Example 3, the difference is that a ZnS optical film with a thickness of 7.7KA is prepared on both sides of the double-polished wafer.
[0038] Microscopic observation of a 7.7KA thick ZnS optical film just taken out of a degassing furnace after high temperature treatment at 350°C. Figure 8 As shown, Figure 8 This is a micrograph of a 7.7KA thick ZnS optical film just taken out of a degassing furnace after being treated at 350°C.
[0039] The ZnS optical film with a thickness of 7.7KA after high temperature insulation treatment at 350℃ was subjected to film pulling experiment using adhesive tape. Fig. 9 As shown, Fig. 9 This is a micrograph of a 7.7KA thick ZnS optical film after film pulling experiment.
[0040] After the film drawing experiment, the ZnS optical film with a thickness of 7.7KA was diced and cleaned and dried with a dicing machine at high speed, and the film effect was observed under a microscope. Fig.10 As shown, Fig.10 This is a micrograph of a 7.7KA thick ZnS optical film after slicing.
[0041] In summary, when the ZnS film thickness is 7.7KA, Figure 8 It can be found that the optical film is in good condition after being kept at 350℃ for 8 hours. Fig. 9 It was found that after the film pulling experiment, the quality of the film layer was still good. Fig.10 It was found that there was no film peeling at the cutting edge and the film was in good condition.
[0042] Example 6 Compared with Example 3, the difference is that a ZnS optical film with a thickness of 13KA is prepared on both sides of the double-polished wafer.
[0043] Microscopic observation of a 13KA thick ZnS optical film just taken out of a degassing furnace after high temperature treatment at 350°C. Fig.11 As shown, Fig.11 This is a micrograph of a 13KA thick ZnS optical film just taken out of a degassing furnace after being treated at 350°C.
[0044] The ZnS optical film with a thickness of 13KA after high temperature insulation treatment at 350℃ was subjected to film pulling experiment using adhesive tape. Fig.12 As shown, Fig.12 This is a micrograph of a 13KA thick ZnS optical film after film pulling experiment.
[0045] After the film drawing experiment, the ZnS optical film with a thickness of 13KA was diced and cleaned and dried with a dicing machine at high speed, and the film effect was observed under a microscope. Fig.13 As shown, Fig.13 This is a micrograph of a 13KA thick ZnS optical film after slicing.
[0046] In summary, when the thickness of the ZnS film is 13KA, Fig.11 It can be found that the optical film is in good condition after being kept at 350℃ for 8 hours. Fig.12 It was found that after the film pulling experiment, the quality of the film layer was still good. Fig.13 It was found that there was no film peeling at the cutting edge and the film was in good condition.
[0047] Through the above experiments, it can be found that the optical film deposited on the wafer surface designed in the experiment can withstand long-term high-temperature degassing well and has high high-temperature resistance reliability.
[0048] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A ZnS optical thin film coating method, characterized in that: The following steps are involved: S1) Clean the substrate with an ion source for 10 min to 15 min at a screen voltage of 650 V to 700 V; S2) performing evaporation coating on the substrate cleaned in step S1) at a temperature of 100° C. to 110° C. and a screen voltage of 700 V to 900 V using an ion source to sequentially form ZnS films on both sides of the substrate; S3) heat-treating the substrate after the coating in step S2).
2. The coating method according to claim 1, characterized in that: In step S1) and step S2), the ion source is a Kaufman source.
3. The coating method according to claim 1, characterized in that: In step S1), the substrate is a double-polished wafer.
4. The coating method according to claim 1, characterized in that: In step S2), when performing the barrier evaporation coating, the current of the ion source is 10A-20A, and the anode voltage of the ion source is 60V-80V.
5. The coating method according to claim 1, characterized in that: In step S2), when performing the barrier evaporation coating, the beam current of the ion source is 45 mA to 60 mA.
6. The coating method according to claim 1, characterized in that: In step S2), the barrier evaporation coating is performed at a current of 400A-500A.
7. The coating method according to claim 1, characterized in that: In step S2), the coating rate of the evaporation barrier coating is less than 10 Å / s.
8. The coating method according to claim 1, characterized in that: In step S2), the thickness of the ZnS film is 1 KA~15 KA.
9. The coating method according to claim 1, characterized in that: In step S3), the temperature of the heat treatment is 300° C. to 400° C., and the time of the heat treatment is 3 h to 6 h.
10. Use of the coating method according to any one of claims 1 to 9 in preparing infrared detector chips.